PENCEGAHAN TINDAK PIDANA KORUPSI DI ERA OTONOMI DAERAH MELALUI PRINSIP GOOD GOVERMENT - Bakhri, Syaiful (Al-Qisth Law Review, 2017)
Corruption has been systemically widespread in era of regional autonomy, prevention model should still be found, not only the nations awareness and moral improvement, but rationally fill it through a series of legislative policies in formulating legislation, enhancing professional law enforcement, and prinsive implementation good governance, which is expected to achieve clean government, from corruption.